Civil engineering problems overseas 1971 proceedings of the converence on civil engineering aspects of development planning organized by the Institution of Civil Engineers in London, 14-16 June 1971. (Institution of Civil Engineers, 1971)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in 1971.